Graft copolymer composition, ABS (Acrylonitrile Butadiene Styrene) resin and preparation method and application of graft copolymer composition and ABS resin

By introducing phenyl organosilane monomer and organosilane polymer into ABS resin, a special composite rubber is formed, which solves the problem of insufficient performance of ABS resin in high-speed impact and puncture protection, and achieves stronger anti-impact and puncture performance.

CN119613630AActive Publication Date: 2025-03-14LIAONING KINGFA SCI & TECH CO LTD +1

Patent Information

Application Number
CN202510157245.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-13
Publication Date
2025-03-14
Estimated Expiration
2045-02-13

AI Technical Summary

Technical Problem

The ABS resin prepared by the existing emulsion polymerization method lacks performance in high-speed impact and puncture-based damage protection, and when increasing the toughness and impact strength of the material, it will lead to a decrease in tensile strength, which poses safety hazards.

Method used

By introducing phenyl organosilane monomer and organosilane polymer into the graft copolymer composition, a special silicone/butadiene/styrene/acrylonitrile composite rubber is formed to improve the high-speed impact and puncture properties of ABS resin.

Benefits of technology

While maintaining the mechanical properties unchanged, the high-speed impact and puncture performance of ABS resin is significantly improved, and is suitable for the fields of peripheral protection of automobile batteries, car pedestrian protection devices, etc.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a graft copolymer composition, ABS (Acrylonitrile Butadiene Styrene) resin as well as a preparation method and application thereof, and belongs to the technical field of high polymer materials. According to the grafted copolymer, a phenyl organosilane monomer and an organosilane polymer are introduced into a monomer, the phenyl organosilane monomer can be polymerized in butadiene rubber, and a small number of silane chain segments exist on the periphery of the phenyl organosilane monomer; in addition, an organosilane polymer is introduced into a grafting shell, a combined grafting group internally contains an organosilicone component and externally contains an organosilicone extended branch chain, and meanwhile, in the grafting polymerization process, a polymerized monomer is pre-emulsified in advance, so that the content of 1, 3, 5-triphenylcyclohexane in a grafted copolymer and final ABS resin can be greatly reduced, and the mechanical property of the ABS resin is improved. The finally prepared ABS resin can keep the mechanical property unchanged, also has relatively strong high-speed impact and puncture resistance, and is especially suitable for being applied to the fields of automobile storage battery periphery protection, automobile pedestrian protection devices, safety helmets for industries such as motorcycles and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a graft copolymer composition and ABS resin, and a preparation method and application thereof. Background Art

[0002] The most critical technologies for electric vehicles are the "three electrics", namely batteries, electronic controls and motors. The general structure of lithium batteries is: cell-module-battery pack. Cell technology is the cornerstone of the battery system, and the process of assembling lithium battery cells into groups is called PACK. The most critical technology in PACK structural design is battery thermal management. Battery thermal management is a technology that solves the problem of thermal dissipation or thermal runaway caused by lithium batteries working at too high or too low temperatures through reasonable design based on the impact of temperature on battery performance, so as to improve the overall performance of the battery. High-voltage insulation resistance is one of the most important technical performance requirements for battery pack structural design, and plastics have good high-voltage insulation. At the same time, another significant advantage of plastics is that it reduces the weight of the battery pack, increases the weight-to-energy density of the battery, and increases the cruising range of electric vehicles.

[0003] ABS resin is one of the potential material choices for the PACK module shell. The main methods for preparing ABS resin are emulsion polymerization and bulk method. The ABS resin rubber prepared by emulsion polymerization has various designs and is more suitable for applications in multiple occasions. However, the disadvantages of ABS resin prepared by emulsion polymerization are also obvious. First, ABS resin mostly uses butadiene rubber and styrene-butadiene rubber as energy-absorbing impact toughening agents, and its cross-linking degree is relatively high. Although it has a certain impact resistance, it is insufficient to protect against puncture-type damage caused by high-speed impact; secondly, if the toughness and impact strength of the material are blindly improved, a large amount of rubber needs to be added for toughening, resulting in a significant decrease in tensile strength, making it difficult to maintain the strength of the overall battery module, so that the battery assembly is exposed to the outside, and there are greater safety hazards; finally, PC / ABS alloys are mostly used in the prior art to solve the above problems, but the introduction of polycarbonate has a negative impact on weight reduction, cost, etc., and therefore cannot meet the technical requirements for comprehensive improvement of multiple defects. Therefore, the present invention provides a graft copolymer composition and ABS resin to solve the above problems from the production technology, thereby increasing the types of ABS resin. Summary of the invention

[0004] The purpose of the present invention is to overcome the shortcomings or defects of the above-mentioned prior art in which ABS resin is prepared by emulsion polymerization, that is, the puncture resistance and high-speed impact resistance are not high enough, and to provide a graft copolymer composition and ABS resin.

[0005] Another object of the present invention is to provide a method for preparing the graft copolymer composition.

[0006] Another object of the present invention is to provide a method for preparing the ABS resin.

[0007] Another object of the present invention is to provide application of the ABS resin.

[0008] To achieve the above object, the present invention is implemented by the following technical solutions: A graft copolymer composition, comprising: A: 95 to 99.9 wt% of at least one graft copolymer A comprising: Based on the graft copolymer A, 50 to 80 wt% of at least one graft base A1 obtained by emulsion polymerization of the following components: A11: 60 to 99.8 wt % of butadiene monomer, based on the graft base A1; A12: 0 to 39.7 wt % of at least one aromatic vinyl monomer, based on the graft base A1; A13: 0.1 to 1 wt % of a phenyl organosilane monomer based on the graft base A1; A14: 0 to 1 wt % of an alkyl organosilane monomer based on the graft base A1; A15: 0.1 to 2 wt% of an organosilane polymer based on the graft base A1; wherein the sum of the weight percentages of A11, A12, A13, A14 and A15 is 100%; and 20 to 50 wt. %, based on the graft copolymer A, of at least one graft shell A2, obtained by emulsion polymerization in the presence of at least one graft base A1: A21: 40 to 99.9 wt % of at least one vinyl aromatic monomer, based on the graft shell A2; A22: 0 to 50 wt% of an acrylonitrile monomer based on the graft shell A2; A23: 0.1 to 2 wt% of an organosilane polymer based on the graft shell A2; Among them, the sum of the weight percentages of A21, A22 and A23 is 100%; The sum of the weight percentages of A1 and A2 is 100%, and C1: 0.1 to 5 wt% of at least one other component C1; The content of 1,3,5-triphenylcyclohexane in the graft copolymer composition is not higher than 5000 ppm.

[0009] In the graft copolymer composition prepared in the present invention, phenyl organic silane monomer and organic silane polymer are first introduced into the graft base A1; the organic silane polymer is introduced in the process of preparing the graft base and the graft shell, and the graft base A1 contains organic silicon components and contains organic silicon extended branches outside, so that similar dissolution allows the organic silane polymer to be enriched at the position of the graft copolymer, and the organic silicon / butadiene / styrene / acrylonitrile composite rubber with a special phase is formed in the ABS resin finally prepared. At the same time, the grafted polymerization monomer is pre-emulsified in advance to improve the mass transfer efficiency of the reaction material and greatly reduce the 1,3,5-triphenylcyclohexane content in the graft copolymer composition, so that the rubber is very likely to be cavitated when subjected to an impact force, thereby absorbing a large amount of energy; the ABS resin prepared by using the graft copolymer composition prepared in the present invention has very strong high-speed impact and puncture resistance while maintaining its mechanical properties.

[0010] It should be noted that 1,3,5-triphenylcyclohexane comes from the side reaction of the graft shell emulsion polymerization. Specifically, it can be adjusted by adjusting the type and content of monomers, increasing the stirring speed in the emulsion polymerization, or by pre-emulsifying the raw materials in the graft shell. The 1,3,5-triphenylcyclohexane content can also be adjusted by post-treatment, such as washing the graft copolymer with a large amount of water.

[0011] It should be noted that the content of 1,3,5-triphenylcyclohexane in the graft copolymer composition of the present invention is not higher than 5000ppm, for example but not limited to not higher than 5000ppm, 4500ppm, 4000ppm, 3500ppm, 3000ppm, 2500ppm, 2000ppm, 1500ppm, 1000ppm, 900ppm, 800ppm, 700ppm, 600ppm, 500ppm, 400ppm, 300ppm, 200ppm, 100ppm, 50ppm, 40ppm, 30ppm, 20ppm or 10ppm, etc. can achieve the present invention.

[0012] It should be noted that A15 and A23 may be the same or different. Preferably, A15 and A23 are the same.

[0013] Further, the at least one grafting base A1 is obtained by the following emulsion polymerization: A11: based on the graft base A1, 60 to 99.8 wt% of butadiene monomer; preferably 65 to 98 wt%, preferably 70 to 96.5 wt%, preferably 75 to 95 wt%, more preferably 80 to 90 wt%; A12: based on the graft base A1, 0 to 39.8 wt% of at least one aromatic vinyl monomer; preferably 1.5 to 31.6 wt%, preferably 2.5 to 27.3 wt%, preferably 3.55 to 22.7 wt%, more preferably 8.3 to 17.9 wt%; A13: based on the graft base A1, 0.1 to 1 wt% of a phenyl organosilane monomer; preferably 0.2 to 0.8 wt%, preferably 0.3 to 0.6 wt%, preferably 0.35 to 0.55 wt%, more preferably 0.4 to 0.5 wt%; A14: based on the graft base A1, 0 to 1 wt% of an alkyl organic silane monomer; preferably 0.1 to 0.8 wt%, preferably 0.2 to 0.6 wt%, preferably 0.3 to 0.55 wt%, more preferably 0.4 to 0.5 wt%; A15: based on the graft base A1, 0.1 to 2 wt% of an organosilane polymer; preferably 0.2 to 1.8 wt%, preferably 0.5 to 1.5 wt%, preferably 0.8 to 1.2 wt%; more preferably 0.9 to 1.1 wt%; The sum of the weight percentages of A11, A12, A13, A14 and A15 is 100%.

[0014] Furthermore, the at least one graft shell A2 is obtained by emulsion polymerization of the following components in the presence of at least one graft base A1: A21: based on the graft shell A2, 40 to 99.9 wt% of at least one aromatic vinyl monomer; preferably 45 to 95 wt%, preferably 50 to 90 wt%, preferably 55 to 85 wt%, more preferably 60 to 80 wt%; A22: based on the graft shell A2, 0 to 50 wt% of an acrylonitrile monomer; preferably 4.8 to 53.2 wt%, preferably 9.5 to 48 wt%, preferably 14.4 to 43.5 wt%, more preferably 19.2 to 38.8 wt%; A23: Based on the graft base A2, 0.1 to 2 wt% of an organosilane polymer; preferably 0.2 to 1.8 wt%, preferably 0.5 to 1.6 wt%, preferably 0.6 to 1.5 wt%, more preferably 0.8 to 1.2 wt%.

[0015] Furthermore, the phenyl organic silane monomer is one or more of dimethylphenylvinylsilane, trimethoxy(4-vinylphenyl)silane and trimethyl(4-vinylphenyl)silane.

[0016] Furthermore, the organosilane polymer is polymethylsiloxane; preferably AFE TM 7610、AFE TM 1520、AFE TM 0020 and AFE TM1410. In some preferred embodiments, the organosilane polymer is a polyether-modified organosilane polymer. Preferably, the polyether-modified organosilane polymer is AFE TM 7610 and / or AFE TM 1520. The ABS resin prepared by its application has better anti-puncture performance.

[0017] Furthermore, the alkyl organic silane monomer is one or more of vinyl trimethoxy silane, vinyl triethoxy silane, vinyl tri(β-methoxyethoxy) silane, vinyl triisopropoxy silane, and γ-methacryloxypropyl trimethoxy silane.

[0018] Specifically, the aromatic vinyl monomer is one or more of styrene, α-methylstyrene or p-methylstyrene.

[0019] The acrylonitrile monomer is one or more of acrylonitrile and / or methacrylonitrile.

[0020] Optionally, one or more optional other components C1 are added. For example, the at least one other component C1 may be selected from one or more of an emulsifier, a reducing agent, a chain transfer agent or an electrolyte.

[0021] In the present invention, commonly used emulsifiers can be selected according to the prior art, such as but not limited to one or more of potassium disproportionate rosin acid, potassium fatty acid, sodium dodecyl sulfonate or sodium dodecylbenzene sulfonate.

[0022] In the present invention, a commonly used chain transfer agent can be selected according to the prior art, such as but not limited to n-dodecyl mercaptan and / or tert-dodecyl mercaptan.

[0023] In the present invention, commonly used electrolytes can be selected according to the prior art, such as but not limited to one or more of sodium carbonate, sodium bicarbonate, sodium hydroxide, potassium carbonate or potassium hydroxide.

[0024] In the present invention, commonly used reducing agents can be selected according to the prior art, such as but not limited to diatomaceous earth, sugars, vitamin C, etc.

[0025] The present invention also provides a method for preparing the graft copolymer composition, comprising the following steps: S1. Before preparing at least one grafting base A1, an initiator is added, and then A11, A12, A13, A14 and A15 are emulsion polymerized in the presence of C1 to obtain a grafting base A1; S2. In the presence of at least one of the grafting bases A1 and C1 described in step S1, A23, pre-emulsified A21 and A22 are added to carry out emulsion polymerization, and after the polymerization is completed, the graft copolymer composition is obtained by high-temperature coagulation.

[0026] In the present invention, commonly used initiators can be selected with reference to the prior art, such as but not limited to one or more of persulfate initiators, azo initiators or peroxide initiators.

[0027] Specifically, the persulfate initiator includes one or more of potassium persulfate, sodium persulfate and ammonium persulfate; the azo initiator includes one or more of azobisisobutylnitrile, azobisisovaleronitrile or azobisisoheptanenitrile; the peroxide initiator includes one or more of isopropyl hydroperoxide, diisopropylbenzene hydroperoxide, tert-butyl hydroperoxide and benzoyl peroxide.

[0028] Specifically, the pre-emulsified A21 and A22 are obtained by uniformly mixing A21, A22, an emulsifier and desalted water.

[0029] Specifically, the temperature of the emulsion polymerization is 50-85° C., and the time of the emulsion polymerization is 24-40 hours.

[0030] Specifically, the high temperature condensation temperature is 65-100°C.

[0031] Specifically, the emulsion polymerization in step S1 is a staged temperature increase polymerization.

[0032] More specifically, the staged temperature polymerization is specifically to heat the system to 50-60°C and react at a constant temperature for 6-10 hours as the first stage polymerization reaction, and the stirring speed is controlled at 90-120rpm; after the first stage polymerization reaction is completed, the system is heated to 65-72°C and reacted at a constant temperature for 10-15 hours as the second stage polymerization reaction, and the stirring speed is 110-130rpm; after the second stage polymerization reaction is completed, the temperature is raised to 75-85°C and the constant temperature reaction is carried out for 10-14 hours as the third stage reaction, and the stirring speed is controlled to 120-180rpm.

[0033] In a preferred embodiment, the graft copolymer is obtained in the form of a powder, i.e., the graft copolymer of step S2 is dried without adding other polymer components. The residual moisture of the obtained graft copolymer powder is less than or equal to 20wt%, preferably less than or equal to 10wt%, more preferably less than or equal to 8wt%.

[0034] Specifically, the residual moisture refers to the weight percentage of water contained in the graft copolymer composition that has not been dehydrated obtained in step S2. Specifically, the residual moisture is determined by means of a suitable analytical device (e.g., a drying and weighing device), and the sample is dried until a constant sample weight is reached within a specified time. For example, the residual moisture of the graft copolymer can be measured at 180° C. in a halogen moisture analyzer HR73 from MettlerToledo until a constant weight is reached within 30 seconds.

[0035] In a specific embodiment, the preparation method comprises the following steps: S1. Add water, initiator, electrolyte, chain transfer agent and emulsifier into a reactor (tank reactor), stir at room temperature until completely dissolved and mixed; introduce nitrogen into the reactor to replace the air so that the oxygen content is less than 10ppm, and then add A11, A12, A13, A14 and A15 in proportion; The reactor was heated to 50-60°C and reacted at a constant temperature for 6-10 hours for the first stage polymerization reaction, and the stirring speed was controlled at 90-120 rpm; after the first stage polymerization reaction, the system was heated to 65-72°C and reacted at a constant temperature for 10-15 hours for the second stage polymerization reaction, and the stirring speed was 110-130 rpm; after the second stage polymerization reaction, the system was heated to 75-85°C and reacted at a constant temperature for 10-14 hours for the third stage reaction, and the stirring speed was controlled at 120-180 rpm. After the reaction, the temperature was lowered and the material was discharged to obtain the graft base A1; S2. The graft base A1 in step S1 is heated to 50-60°C, and an initiator, a chain transfer agent, a reducing agent, an electrolyte, A23, pre-emulsified A21 and A22 (obtained by uniformly mixing A21, A22, an emulsifier and desalted water) are continuously added dropwise for 1.5-2.5 hours. After the heating is completed, the reaction is continued for 2-4 hours, and then the temperature is raised to 63-68°C and the reaction is continued for 1.5-2.5 hours to obtain a grafted latex; the grafted latex is added to a coagulant reactor, heated to 70-80°C, sulfuric acid is gradually added thereto, and the addition is completed within 1.5-2.5 hours, and the temperature is raised to 90-99°C and maintained at the temperature for 1.5-3 hours. The suspension of water and graft copolymer composition powder is centrifuged and dehydrated to obtain a wet powder with a moisture content of 25-40%, which is washed and dried to obtain a graft copolymer composition with a moisture content of less than 1%.

[0036] The present invention also provides an ABS resin, wherein the ABS resin comprises: D: 65 to 85 wt% of a styrene-acrylonitrile copolymer; B: 15 to 35 wt % of the above graft copolymer composition or the graft copolymer composition prepared by the above preparation method; F: 0 to 20 wt% of at least one other polymeric component F, and C2: 0 to 10 wt % of at least one other component C2.

[0037] Specifically, the weight content of styrene in the styrene-acrylonitrile copolymer is 72 to 78 wt %.

[0038] In a specific embodiment, the other polymeric component F is selected from polycarbonate, polyamide and polyester.

[0039] In a specific embodiment, the other component C2 includes, but is not limited to, one or more of fillers, reinforcing agents, dyes, lubricants, release agents, stabilizers, antioxidants, UV absorbers, plasticizers, impact modifiers, antistatic agents, flame retardants, bactericides or foaming agents.

[0040] Specifically, the filler or reinforcing agent includes, but is not limited to, one or more of silicate, amorphous silicon dioxide, calcium silicate, quartz, mica, metal oxide, metal hydroxide, graphite, barium sulfate, calcium carbonate, magnesium carbonate, talc, kaolin, carbon fiber or glass fiber.

[0041] Specifically, the pigment includes but is not limited to one or more of titanium dioxide, phthalocyanine, ultramarine, iron oxide or carbon black.

[0042] Specifically, the stabilizer includes but is not limited to one or more of benzophenone, salicylate, benzotriazole or benzophenone.

[0043] Specifically, the release agent includes, but is not limited to, fatty acids having 12 to 30 carbon atoms, salts thereof, and derivatives thereof, such as stearic acid, stearate, palmitic acid, palmitate, stearyl alcohol, amide wax, polyolefin wax, and the like.

[0044] In the present invention, commonly used antioxidants can be selected according to the prior art, such as but not limited to one or more of hindered phenol antioxidants, phosphite antioxidants or thioester antioxidants.

[0045] Specifically, the hindered phenol antioxidant is one or more of N,N'-hexamethylenebis(3,5-di-tert-butyl-4-hydroxyphenylpropionamide, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], triethylene glycol bis-3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate, β-(4-hydroxy-3,5-di-tert-butylphenyl)propionate n-octadecyl or spiroethylene glycol bis[β-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate].

[0046] Specifically, the phosphite antioxidant is 2,4-di-tert-butylphenol and / or bis(2,6-di-tert-butyl-4-tolyl)pentaerythritol phosphite.

[0047] Specifically, the thioester antioxidant is one or more of distearyl thiodipropionate, dilauryl thiodipropionate or pentaerythritol dodecapropylthioate.

[0048] In the present invention, commonly used lubricants can be selected according to the prior art, such as but not limited to at least one of amide lubricants, stearate lubricants, ester lubricants or silicone lubricants.

[0049] The present invention also provides a method for preparing the ABS resin, comprising the following steps: The graft copolymer composition, other polymer components F of the styrene-acrylonitrile copolymer and other components C2 are uniformly mixed and granulated by extrusion to obtain ABS resin.

[0050] Furthermore, the extrusion granulation adopts a twin-screw extruder.

[0051] Furthermore, the extrusion temperature is 200-300°C.

[0052] Furthermore, the screw speed of the twin-screw extruder is 200-300 rpm.

[0053] Furthermore, the screw length-to-diameter ratio of the twin-screw extruder is 18:1.

[0054] The present invention relates to the use of the above ABS resin for preparing household goods, electronic components, household appliances, gardening equipment, medical technology equipment, motor vehicle parts and body parts. In particular, the above ABS resin can be used to prepare articles (such as molded products) with puncture resistance. In particular, it can be used to prepare automotive battery peripheral protection, automotive pedestrian protection devices, motorcycle and other industries safety helmets.

[0055] Compared with the prior art, the present invention has the following beneficial effects: The invention provides a graft copolymer composition. By introducing a phenyl organic silane monomer, an organic silane phase region is formed inside the rubber during polymerization, and an organic silane segment is formed outside the rubber. An organic silane polymer added externally is combined to form an organic silicon / butadiene / styrene / acrylonitrile composite rubber with a special phase state in an ABS system. The ABS resin prepared from the rubber has very strong anti-puncture performance while maintaining its relatively high mechanical properties. The ABS resin can be widely used in the fields of peripheral protection of automobile batteries, automobile pedestrian protection devices, safety helmets for motorcycles and the like. DETAILED DESCRIPTION

[0056] The present invention is further described in detail below in conjunction with specific examples, which are only used to explain the present invention and are not used to limit the scope of the present invention. The test methods used in the following examples are conventional methods unless otherwise specified; the materials and reagents used are reagents and materials that can be obtained from commercial channels unless otherwise specified.

[0057] The raw materials used in each embodiment and comparative example are: A11: Butadiene monomer, industrial grade butadiene, purity greater than 96%, Huarui Chemical; A12: aromatic vinyl monomer, styrene, purity greater than or equal to 99%, purchased from Aladdin Reagent Company; A13: Phenyl organosilane monomer A13-1: trimethoxy(4-vinylphenyl)silane, purity greater than or equal to 99%, purchased from Aladdin Reagent Company; A13-2: dimethylphenylvinylsilane, purity greater than or equal to 99%, purchased from Aladdin Reagent Company; A13-3: trimethyl (4-vinylphenyl) silane, purity greater than or equal to 99%, purchased from Aladdin Reagent Company; A14: alkyl organosilane monomer, vinyl trimethoxysilane, purity greater than or equal to 99%, purchased from Aladdin Reagent Company; A15: Organosilane polymer A15-1: AFE TM 7610, purchased from The Dow Chemical Company; A15-2: AFE TM 1520, purchased from The Dow Chemical Company; A15-3: AFE TM 0120, purchased from The Dow Chemical Company; Other surfactants S-1: polyvinyl alcohol ether surfactant, ABEX DBR-Z, purchased from Solvay; Other surfactants S-2: 2,5,8,11-tetramethyl-6-dodecene-5,8-diol, purity greater than or equal to 99%, purchased from Aladdin Reagent Company; A21: Styrene monomer, industrial grade styrene, purity greater than 96%, Baolai Chemical; A22: acrylonitrile monomer, acrylonitrile, purity greater than or equal to 99%, purchased from Aladdin Reagent Company; A23: Organosilane polymer A23-1: AFE TM 7610, purchased from The Dow Chemical Company; A23-2: AFE TM 1520, purchased from The Dow Chemical Company; A23-3: AFE TM 0120, purchased from The Dow Chemical Company; Other surfactants S-3: organosiloxane surfactant, TEGOPREN 5840, purchased from Evonik; Other surfactants S-4: 2,5,8,11-tetramethyl-6-dodecene-5,8-diol, purity greater than or equal to 99%, purchased from Aladdin Reagent Company; Initiator: sodium persulfate, commercially available; Other components C1 Electrolyte: sodium carbonate, commercially available; Emulsifier: potassium disproportionate rosin acid, commercially available; Chain transfer agent: tert-dodecyl mercaptan, commercially available; Reducing agent: bleaching powder, commercially available; Styrene-acrylonitrile copolymer: PN-118, styrene content of 75%, purchased from Chi Mei, Taiwan; Other components C2: Antioxidant: pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate (hindered phenol antioxidant) and tris(2,4-di-tert-butylphenyl) phosphite (phosphite antioxidant) are compounded in a weight ratio of 1:1 and are commercially available; Lubricant: ethylene bisstearic acid amide, commercially available; it should be noted that the raw materials used in the parallel experiments of the embodiment and the comparative example are the same commercially available products.

[0058] Examples 1 to 11 and Comparative Examples 1 to 8 In the examples and comparative examples, the graft copolymer composition is prepared according to the formulations in Tables 1 to 2 by the following method, comprising the following steps: S1. Based on the grafting base A1, 100 wt% of water, 1 wt% of initiator, 0.6 wt% of chain transfer agent, 0.4 wt% of electrolyte and 0.4 wt% of emulsifier are added to a reactor (aqueous reactor), and stirred at room temperature until completely dissolved and mixed; nitrogen is introduced into the reactor to replace the air so that the oxygen content is less than 10 ppm, and then A11, A12, A13, A14 and A15 are added in proportion; The reactor was heated to 55°C and kept at this temperature for 9 hours for the first stage polymerization reaction, and the stirring speed was controlled at 105 rpm; after the first stage polymerization reaction, the system was heated to 70°C and kept at this temperature for 12 hours for the second stage polymerization reaction, and the stirring speed was controlled at 120 rpm; after the second stage polymerization reaction was completed, the system was heated to 75°C and kept at this temperature for 12 hours for the third stage reaction, and the stirring speed was controlled at 130 rpm. After the third stage reaction, the system was cooled and discharged to obtain the grafted base A1; S2. The graft base A1 in step S1 is heated to 55°C, and 0.7wt% initiator, 0.6wt% chain transfer agent, 0.8% reducing agent, 0.2% electrolyte, A23, pre-emulsified A21 and A22 (obtained by uniformly mixing A21, A22, 0.4wt% emulsifier based on graft copolymer A and 120wt% desalted water) are added dropwise continuously for 2h. After heating, the reaction is continued for 3h, and then the temperature is raised to 65°C for reaction for 2h to obtain a graft latex. ; Take the grafted latex and add it into a coagulation reactor, heat it to 75°C, gradually add sulfuric acid into it, add it within 2 hours, and raise the temperature to 95°C and maintain the temperature for 2 hours to obtain a suspension of water and graft copolymer composition powder. After centrifugal dehydration, a wet powder with a moisture content of 25% to 40% is obtained. Then, water twice the weight of the wet powder is added for washing. After washing, centrifugal dehydration is performed again. After three cycles, the washed wet powder is dried in a fluidized bed dryer at 60°C for 2 hours to obtain a graft copolymer composition with a moisture content of less than 1%.

[0059] Determination of 1,3,5-triphenylcyclohexane content in the graft copolymer composition: 5 mg of the graft copolymer composition prepared in each example and comparative example was put into 20 mL of anhydrous ethanol, shaken for 5 hours, filtered with filter paper after standing, and the clarified filtrate was tested by gas chromatography. Chromatographic column: Aglient HP-1 column (50 m*0.25 mm, 0.5 μm, Agilent Technologies, Inc., USA); carrier gas: nitrogen; column flow rate: 1.0 mL / min; column box temperature heating program: initial temperature 40 ℃, maintain for 5 min, increase to 150 ℃ at 10 ℃ / min, and then increase to 220 ℃ at 15 ℃ / min; vaporizer temperature: 280 ℃; detector temperature 300 ℃; split ratio 50:1; injection volume: 1 μL; cylinder pressure: 0.5~1.5 MPa; quantitative method: chromatographic peak area external standard method, calculate the concentration of 1,3,5-triphenylcyclohexane in the graft copolymer composition, and the result is calculated in ppm.

[0060] Table 1 Amount of each component in the graft copolymer composition in Examples 1 to 10 (unit: weight percentage)

[0061] Note: The weight percentages of A1 and A2 are based on graft copolymer A, and graft copolymer A accounts for more than 95wt% of the graft copolymer composition.

[0062] Table 2 Amount of each component in the graft copolymer composition in Comparative Examples 1 to 7 (unit: weight percentage)

[0063] Note: The weight percentages of A1 and A2 are based on graft copolymer A, and graft copolymer A accounts for more than 95wt% of the graft copolymer composition.

[0064] The preparation of the graft copolymer composition in Comparative Example 8 is the same as that in Example 1, except that A21, A22, emulsifier and desalted water are directly added in step S2 without pre-emulsification, and the content of 1,3,5-triphenylcyclohexane is 5102 ppm.

[0065] The graft copolymer composition described in Example 11 is a suspension of water and graft copolymer composition powder obtained by condensation and dehydration of the graft latex obtained in step S2 of Comparative Example 8, and a wet powder with a moisture content of 25%-40% is obtained after centrifugal dehydration, and then water 12 times the weight of the wet powder is added for washing, and then centrifugal dehydration is performed again after washing. After 5 cycles, the washed wet powder is dried at 60°C for 2h in a fluidized bed dryer to obtain a graft copolymer composition with a moisture content of less than 1%; the 1,3,5-triphenylcyclohexane content is 4428ppm.

[0066] Specifically, the amounts of each component in A1 and A2 are shown in Tables 3-4.

[0067] Table 3 Amount of each component in A1 (unit: weight percentage)

[0068] Note: The weight percentages of A11, A12, A13, A14, A15, S-1 and S-2 are based on A1.

[0069] Table 4 Amount of each component in A2 (unit: weight percentage)

[0070] Note: The weight percentages of A21, A22, A23, S-3 and S-4 are based on A2.

[0071] Examples 12 to 24 and Comparative Examples 9 to 16 In the embodiments and comparative examples, the ABS resin is prepared according to the formulations in Tables 5 to 6 by the following method, comprising the following steps: The graft copolymer composition, styrene-acrylonitrile copolymer and other component C2 are uniformly mixed, and granulated by extrusion through a twin-screw extruder to obtain ABS resin; the extrusion temperature is 200-300°C, the screw speed is 250rpm, and the screw aspect ratio is 18:1.

[0072] Table 5 ABS resin formulations in Examples 12 to 24 (unit: weight percentage)

[0073] Table 6 ABS resin formulations in Comparative Examples 9 to 16 (unit: weight percentage)

[0074] Performance Testing The ABS resin prepared in the above examples and comparative examples was subjected to performance tests, and the specific test items and test methods are as follows: 1. Test method: (1) Mechanical properties test: ABS resin was placed in 80 o C oven drying for 2 hours, and then using a KraussMaffei injection molding machine, select ISO standard mechanical mold at 220 o C, injection molding was performed under medium and high pressure and speed to obtain tensile and impact specimens that meet ISO standards. The specimens were kept at room temperature at 23 o C, constant humidity RH. 50% for 24 hours, and then the tensile strength test was carried out according to ISO 527-2 2012 at a tensile speed of 50 mm / min; the notched impact strength test was carried out according to ISO 178 2010.

[0075] (2) Puncture resistance test: evaluated by multi-axial impact strength test (MAI), measured according to ISO 6603-2023 using a 3.2 mm thick, 10 cm diameter test piece, with a drop hammer diameter of 12.5 mm and measured at 4.4 m / s. The results are expressed in % ductility and absorbed energy values. This method provides a means to characterize the amount of energy absorbed by the material under multi-axial deformation conditions and the form of material failure. The applied deformation is high-speed puncture. If the material exhibits 0% ductility, that is, 100% brittleness and small absorbed energy, it cannot be used in protective components such as battery packs and helmets. The final test results are calculated as the average test results of 5 test pieces.

[0076] 2. Test results The test results are shown in Table 7.

[0077] Table 7 Experimental results of various embodiments and comparative examples

[0078] It can be seen from Table 7 that the content of 1,3,5-triphenylcyclohexane in the graft copolymer composition prepared by the present invention is no more than 5000 ppm, and the ABS resin prepared by mixing and extruding the styrene-acrylonitrile copolymer has good mechanical properties and puncture resistance.

[0079] It can be seen from Comparative Examples 9 to 11 that if no organosilane polymer is added to the graft shell or other surfactants are used instead of the organosilane polymer in the present invention, the content of 1,3,5-triphenylcyclohexane in the obtained graft copolymer composition increases, and the mechanical properties of the ABS resin finally obtained are slightly reduced, but the puncture resistance is significantly reduced.

[0080] It can be seen from Comparative Examples 12 to 15 that if other substances are used in the graft base to replace the phenylalkylsilane monomer or the organosilane polymer is not added to the graft base or other surfactants are used to replace the organosilane polymer in the present invention, the content of 1,3,5-triphenylcyclohexane in the graft copolymer composition increases, and the mechanical properties of the ABS resin finally obtained are slightly reduced, but the puncture resistance is significantly reduced.

[0081] It can be seen from Comparative Example 16 that if A21 and A22 in the graft shell are not pre-emulsified, the content of 1,3,5-triphenylcyclohexane increases, and the mechanical properties of the ABS resin do not meet expectations, and the anti-puncture performance is significantly different from that of the embodiment.

[0082] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A graft copolymer composition, characterized in that: The graft copolymer composition comprises: A: 95 to 99.9 wt% of at least one graft copolymer A comprising: Based on the graft copolymer A, 50 to 80 wt% of at least one graft base A1 obtained by emulsion polymerization of the following components: A11: 60 to 99.8 wt % of butadiene monomer, based on the graft base A1; A12: 0 to 39.8 wt % of at least one aromatic vinyl monomer, based on the graft base A1; A13: 0.1 to 1 wt % of a phenyl organosilane monomer based on the graft base A1; A14: 0 to 1 wt % of an alkyl organosilane monomer based on the graft base A1; A15: 0.1 to 2 wt% of an organosilane polymer based on the graft base A1; wherein the sum of the weight percentages of A11, A12, A13, A14 and A15 is 100%; and 20 to 50 wt. %, based on the graft copolymer A, of at least one graft shell A2, obtained by emulsion polymerization in the presence of at least one graft base A1: A21: 40 to 99.9 wt % of at least one vinyl aromatic monomer, based on the graft shell A2; A22: 0 to 50 wt% of an acrylonitrile monomer based on the graft shell A2; A23: 0.1 to 2 wt% of an organosilane polymer based on the graft shell A2; Among them, the sum of the weight percentages of A21, A22 and A23 is 100%; The sum of the weight percentages of A1 and A2 is 100%, and C1: 0.1 to 5 wt% of at least one other component C1; The content of 1,3,5-triphenylcyclohexane in the graft copolymer composition is not higher than 5000 ppm.

2. The graft copolymer composition according to claim 1, characterized in that: The phenyl organic silane monomer is one or more of dimethylphenylvinylsilane, trimethoxy(4-vinylphenyl)silane and trimethyl(4-vinylphenyl)silane.

3. The graft copolymer composition according to claim 1, characterized in that: The organosilane polymer is polymethylsiloxane.

4. The graft copolymer composition according to claim 1, characterized in that: The alkyl organic silane monomer is one or more of vinyl trimethoxy silane, vinyl triethoxy silane, vinyl tri(β-methoxyethoxy) silane, vinyl triisopropoxy silane, and γ-methacryloxypropyl trimethoxy silane.

5. The graft copolymer composition according to claim 1, characterized in that: The aromatic vinyl monomer is one or more of styrene, α-methylstyrene or p-methylstyrene.

6. The graft copolymer composition according to claim 1, characterized in that: The acrylonitrile monomer is one or more of acrylonitrile and / or methacrylonitrile.

7. The graft copolymer composition according to claim 1, characterized in that: The other components C1 include one or more of an emulsifier, a reducing agent, a chain transfer agent or an electrolyte.

8. A method for preparing the graft copolymer composition according to any one of claims 1 to 7, characterized in that: The steps include: S1. Before preparing at least one grafting base A1, an initiator is added, and then A11, A12, A13, A14 and A15 are emulsion polymerized in the presence of C1 to obtain a grafting base A1; S2. In the presence of at least one of the grafting bases A1 and C1 described in step S1, A23, pre-emulsified A21 and A22 are added for emulsion polymerization, and after the polymerization is completed, the graft copolymer composition is obtained by high-temperature coagulation; the temperature of the high-temperature coagulation is 65~100℃.

9. The preparation method according to claim 8, characterized in that: The emulsion polymerization in step S1 is staged temperature-raising polymerization.

10. The preparation method according to claim 9, characterized in that: The staged temperature-raising polymerization is specifically as follows: heating the temperature to 50-60° C. and reacting at the constant temperature for 6-10 hours as the first stage polymerization reaction, and controlling the stirring speed at 90-120 rpm; after the first stage polymerization reaction is completed, heating the system to 65-72° C. and reacting at the constant temperature for 10-15 hours as the second stage polymerization reaction, and stirring the system at the stirring speed of 110-130 rpm; after the second stage polymerization reaction is completed, heating the system to 75-85° C. and reacting at the constant temperature for 10-14 hours as the third stage reaction, and controlling the stirring speed to 120-180 rpm.

11. An ABS resin, characterized in that: The ABS resin comprises: D: 65 to 85 wt% of a styrene-acrylonitrile copolymer; B: 15 to 35 wt % of the graft copolymer composition according to any one of claims 1 to 7 or the graft copolymer composition prepared by the method for preparing the graft copolymer composition according to any one of claims 9 to 10; F: 0 to 20 wt% of at least one other polymeric component F, and C2: 0 to 10 wt % of at least one other component C2.

12. The ABS resin according to claim 11, characterized in that: The further polymeric component F is selected from the group consisting of polycarbonates, polyamides and polyesters.

13. A method for preparing ABS resin, characterized in that: The steps include: The styrene-acrylonitrile copolymer, the graft copolymer composition according to any one of claims 1 to 7 or the graft copolymer composition prepared by the preparation method of the graft copolymer composition according to any one of claims 9 to 10, other polymer components F and other components C2 are uniformly mixed and extruded and granulated to obtain ABS resin.

14. Use of the ABS resin according to claim 12 in the preparation of automobile battery peripheral protection, automobile pedestrian protection device, and safety helmet for the motorcycle industry.

Citation Information

Patent Citations

  • Process for producing resin varnish containing semi-ipn composite thermosetting resin and, provided using the same, resin varnish for printed wiring board, prepreg and metal-clad laminate

    CN101668806A

  • Styrene-based copolymer and thermoplastic resin composition including the same

    CN104693334A

  • Preparation method of polybutadiene latex, polybutadiene latex and ABS (Acrylonitrile Butadiene Styrene)

    CN112876609A

  • Graft copolymer composition, ABS (Acrylonitrile Butadiene Styrene) resin and preparation method and application of graft copolymer composition and ABS resin

    CN118184892A

  • Graft copolymer and thermoplastic resin composition

    JP1997136928A

Cited By

  • PC / ABS (polycarbonate / acrylonitrile butadiene styrene) composition as well as preparation method and application thereof

    CN120699405A

  • Grafted copolymer composition, ABS resin, and preparation method therefor and the use thereof

    WO2026170723A1